American beauty - Ball, Alan 1957-; Mendes, Sam 1965-; Bening, Annette 1958-; Spacey, Kevin 1959-; Bentley, Wes 1978-; Birch, Thora 1982- (Universal Home Video, 2000)
A biting, penetrating and often humorous look at contemporary life in suburban America. When midlife crisis hits, Lester Burnham's fascination with a young girl spurs him to make some major changes in his life
Originally released as a motion picture in 1999. - DVD special features include behind the scenes featurette with interviews from the cast and crew, commentary by the director and writer, storyboard presentation, digital screenplay, cast and crew biographies, 2 theatrical trailers, production notes, and more
Annette Bening, Kevin Spacey, Wes Bentley, Thora Birch, Chris Cooper, Peter Gallagher, Allison Janney Mena Suvari
Conrad L. Hall, photography; Tariq Anwar and Chris Greenbury, editors; Thomas Newman, music
Keywords: Suburban life / United States / drama; Midlife crisis / drama; Feature films; USA; DVD-Video